HUBUNGAN ETIKA DENGAN PROFESI SERTA SIKAPNYA DAN PERMASALAHAN DALAM MASYARAKAT MODERN DI ERA DIGITALISASI - Bandi Siswanto; Arhab Ramy Ramdhani; Emi Kholilah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Ethics is a conception of whether a person's temperament or behavior is good or bad. Professional ethics is an ethical attitude that is an integral part of one's attitude towards living one's life as a professional. Continuation of an outdated system. Legal professionals are part of the justice system whose role is to help disseminate a system that is considered outdated because it contains many law enforcement provisions that are no longer appropriate. Advances in computer science and technology can give rise to new types of crime. One of the aspects highlighted by ethics and morals regarding a person's behavior is in the field of skilled work called a profession. Because the profession is a job about theoretical and technical expertise, which relies on honesty, so the dependence and expectations of people who need help are very large in order to implement the system of justice, so that the bearers of a profession are required to have certain prerequisites in carrying out and carrying out their duties and responsibilities. professional function, so that they truly work professionally in their field. Social change is a change that occurs as a variation of life events that have been accepted due to changes in geographic, cultural, material conditions, population composition, ideology or by diffusion or new discoveries in society. Law as social engineering is an effort to deal with legal problems that occur where certain existing laws are formed.